Advancing Social Functionality Via Agent‐Based Parametric Semiology. (March 2016) - Schumacher, Patrik
Abstract : With the launch of Parametricism 2.0, Guest‐EditorPatrik Schumacher asserts how Parametricism as a movement now needs to shift its main focus from computation and technological advancement towards social function. Here he advocates how Parametricism should realise its semiotic potential, with the power to express complex spatial arrangements in large‐scale projects and a full spectrum of programmes for diverse users.